(untitled) (Jurnal De Jure Muhammadiyah Cirebon, 2022)
The crime of assault is quite rampant in Indonesia. The reasons behind it are also varied, starting from intentional acts to mere retaliation for perceived wrongdoings or the pain suffered by the assailant. Acts of assault can be carried out individually or collectively. So, what happens when someone or a group of individuals assault a thief caught red-handed in the act of theft? Can the act of assault be justified legally, or does it result in other criminal acts? This research will specifically discuss the legal consequences of assault committed against criminal perpetrators. Through a juridical examination of the act of assault by individuals who directly apprehend the criminal, the aim is to analyze legal issues related to assault carried out by those who catch criminals in the act. In order to establish a common understanding of assault, it is necessary to examine the applicable legal provisions. Therefore, the research methodology used is normative juridical research. This method involves analyzing the law as it is formulated into legal materials, such as legislation, particularly the Indonesian Criminal Code (KUHP), relevant court decisions, and various principles and norms that serve as benchmarks for human behavior deemed appropriate. The results of this research aim to determine whether the act of assault carried out by individuals who directly apprehend criminal perpetrators can be justified, even when done to apprehend a perpetrator caught in the act of a crime. Criminal sanctions can be imposed on such actions, regardless of the underlying reasons, if they meet the criteria of assault as defined in Article 170 of the Indonesian Criminal Code. Therefore, this research will culminate in determining whether the act of apprehension permits members of the public (outside law enforcement officials) to use violence or engage in assault during the arrest of a criminal. The legitimate and applicable legal procedures for conducting arrests will be elaborated upon. This is important to ensure that individuals apprehended in the act of a crime by an individual or the public at large are dealt with fairly and in accordance with the principles, norms, and applicable laws and regulations. Keywords: vigilante, KUHP, criminals